Extravagant : discovering a life of dangerous generosity - Boyd, Brady (Howard Books/Atria Books, 2020)
From the senior pastor of New Life Church, a revolutionary book that redefines the notion of extravagance by using the parable of the Good Samaritan to demonstrate how to live a truly compassionate and selfless life of giving freely without expecting anything in return. We all know people in our lives who have "yes" faces. They are calm but energetic, present but still purposeful with their time. They are curious. They ask questions. They're genuine in their desire to know about you--how you're doing, what you're up to, how you feel. Even with full lives of their own, they somehow still have the energy to inquire about others. These are extravagant people. In Extravagant, Pastor Brady Boyd shows us that by constantly offering up our time, talents, and hearts we can live life more like these exceptional people. Drawing on the parable of the Good Samaritan, he encourages us to stop living a life driven by selfish desire and start building lasting relationships that will be spiritually fulfilling. Discover how to begin this transformation by ceasing to be a passerby and become one who pauses in the course of daily life. By embracing the spirit of generosity, Pastor Boyd shows us that the path to a happier life is by living closer to God's vision and building a community that will be there in times of need. Timely, thought-provoking, and inspiring, Boyd's uplifting message of reclaiming your connections to others and being a good neighbor is just the remedy we need in today's fractured culture and troubled times.